Designing Digital Learning Media with Canva and Project-Based Learning to Enhance IPAS Instruction - Irma Aprilda Sinaga; Agus Junaidi; Derlina Derlina (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: Student learning outcomes in the topic of Energy and Its Transformations remain consistently low in Indonesian vocational high schools. One of the key challenges is the predominant use of conventional teaching methods and the minimal use of engaging digital tools. This results in low student participation and limited conceptual understanding.Aims: This study aimed to develop and evaluate interactive learning media using Canva, integrated with the Project-Based Learning (PjBL) model, to improve student engagement and learning outcomes in IPAS (Natural and Social Sciences) for Grade X students.Methods: The study employed a Research and Development (R&D) approach using the ADDIE model, covering Analysis, Design, Development, Implementation, and Evaluation. The media included interactive features such as visual simulations, drag-and-drop tasks, embedded videos, and quizzes with instant feedback. It was validated by three subject-matter experts and tested in stages: individual trials (3 students), small-group trials (6 students), and a field test with 64 students divided into experimental and control groups. Instruments included expert validation sheets, practicality questionnaires, pretest and posttest assessments. Data were analyzed using descriptive statistics and independent t-tests.Results: The media received a validation score of 88.7% (highly feasible). Practicality ratings from teachers and students averaged 89.4%. The experimental group showed significantly higher posttest scores than the control group (p < 0.05), with moderate learning gains.Conclusion: Canva-based interactive media, when combined with the PjBL model, is valid, practical, and effective for enhancing engagement and learning outcomes in vocational science education. It is suitable for broader implementation across similar educational settings.